Respostas
respondido por:
23
{a+2b=7
3a-b=-7 multiplicando por 2
a + 2b=7
6a - 2b = -14
7a = -7 ⇒ a = -7/7 ⇒ a = -1
Logo a + 2b = 7 ⇒ 2b = 7 + 1 ⇒ 2b = 8 ⇒ b = 8/2 b = 4
se 2a - 3b =m
2 . -1 - 3 . 4 = m
m = -2 - 12
m = -14
3a-b=-7 multiplicando por 2
a + 2b=7
6a - 2b = -14
7a = -7 ⇒ a = -7/7 ⇒ a = -1
Logo a + 2b = 7 ⇒ 2b = 7 + 1 ⇒ 2b = 8 ⇒ b = 8/2 b = 4
se 2a - 3b =m
2 . -1 - 3 . 4 = m
m = -2 - 12
m = -14
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás